Boosting curcumin activity against human prostatic cancer PC3 cells by utilizing scorpion venom conjugated phytosomes as promising functionalized nanovesicles. (31st December 2022) - Al-Rabia, Mohammed W.; Alhakamy, Nabil A.; Rizg, Waleed Y.; Alghaith, Adel F.; Ahmed, Osama A. A.; Fahmy, Usama A.
Abstract: Prostate cancer (PC) is emerging as one of the leading causes of mortality and morbidity worldwide. Curcumin (CUR) is a well-known phytochemical, and scorpion venom (SV) is a natural peptide with proven anticancer properties. However, these natural bioactive agents are limited by low solubility, low bioavailability, poor thermal stability, and short half-lives. Therefore, the aim of this study was to fabricate SV-conjugated CUR phytosomes as promising functionalized nanovesicles and assess their anticancer efficacy in human prostatic cancer PC3 cells. CUR-Phytosome-SV was fabricated using experimental design software in which the zeta potential and particle sizes were used as dependent variables. The anticancer effect of the fabricated formulation was determined by performing a tetrazolium (MTT) assay, cell cycle analysis, annexin V staining, and examining the expression levels of Bcl-associated X-protein (Bax), p53, caspase-3, B-cell lymphoma 2 (Bcl-2), nuclear factor kappa beta (NF-kB), and tumor necrosis factor alpha (TNF-α). The particle size of the nanoconjugates was found to be in the range of 137.5 ± 7.9 to 298.4 ± 11.9 nm, and the zeta potential was 2.9 ± 0.1 to 26.9 ± 1.2 mV. The outcome of the MTT assay showed that curcumin–Phospholipon ® –scorpion venom (CUR–PL–SV) exhibited a satisfactory level of cytotoxicity, and the IC50 was found to be lower than CUR and PL-SV individually. Cell cycle analysis showed predominantly cell cycle arrest at the G2-M and pre-G1 phases. In contrast, annexin V staining showed significant early and late apoptosis events in addition to increased necrosis when PC3 cells were treated with CUR–PL–SV. Reverse-transcriptase polymerase chain reaction (RT-PCR) analysis showed a reduction in expression of Bax, p53, caspase-3, NF-kB, TNF-α, and an increase in Bcl-2 expression. Moreover, a MMP analysis showed a reduction in mitochondrial permeability and hence confirmed the superior anticancer potential of CUR–PL–SV. Thus, the present study showed significant anticancer potency of SV-conjugated CUR phytosomes against human prostatic cancer PC3 cells, making it a novel treatment approach for PC.